COVID-19 Pandemic: A Positive Influence on Lifestyle, Economy, Administration & Environment; An Overview - Kunal Dwari (Institute of Medico-legal Publications Pvt Ltd, 2020)
Summary: On the December 31st 2019, World Health Organization (WHO) was alerted about a bunch ofnewly arrived pneumonia cases in city of Wuhan, China. The Severe Acute Respiratory Syndrome (SARS)later became well known as COVID-19. The causative virus was isolated on 7th January, which was thenovel coronavirus ‘SARS-CoV-2. Initial evidences suggested it is a zoonotic disease originating from batswhich was then transmitted to humans. As of June 27 2020, the number of Identified COVID-19 casesglobally were 9,815,826 of which active number of cases were 4,018,892 and total number of deaths were494,118. To contain the spread of this disease many nations around the world introduced partial/completelockdown. India declared nationwide lockdown on 25 march 2020, which is considered as the world’slargest lockdown. This led to too much distress in the society and nation. But every coin has 2 sides, todaylet’s flip the coin and have a look at the unnoticed head of the coin. This article is the review of numerousarticles available online highlighting the disguised positive impacts under the following domain:• Lifestyle and health related positive impact includes hygiene practices, attitude of good health andimmunity.• Positive Impact on Administration & Health sector indicating the lacunas of poor health infrastructure.• Social & Personal impact leading to better personality development.• Impact related to Lockdown which includes good environmental changes, trade and work-relatedpositivity